Influence of Lactic Acid Bacteria Fermentation on Physicochemical Properties and Antioxidant Activity of Chickpea Yam Milk - Xue Zhang; Shuai Zhang; Bijun Xie; Zhida Sun (Journal of Food Quality)
This study aimed to evaluate the influence of lactic acid bacteria fermentation on the physicochemical properties and antioxidant activity of chickpea yam milk. Four groups of chickpea milk were prepared through fermentation with lactic acid bacteria for quality and functionality improvement. Results indicate that the polysaccharide content of four samples declines during the fermentation process, and their infrared spectrums are similar with a slight difference in the transmittances of some characteristic bands. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) profiles of four samples with 24 h fermentation showed a band disappearance in the range of 94.3 KDa and generation of many small-molecule peptides, revealing the protein degradation during fermentation. The moderate enzymatic hydrolysis had no adverse effect on the texture and color of the samples. A substantial increase in DPPH, ABTS radical scavenging rates, and FRAP value was observed after 12 h fermentation, especially the CPBY sample. The present results indicate that lactic acid bacteria fermentation can be used to improve the physicochemical properties of samples and enhance their antioxidant activity.